Surgical Treatment of the Glenohumeral Joint for Indications of Instability and Pain in Hypermobile Ehlers-Danlos Syndrome - Systematic Review - Jabłoński, Jędrzej; Nadolny, Filip; Kania, Martyna; Grubski, Damian; Bartkowiak, Hanna; Adamowska, Agnieszka; Ziarnik, Kacper; Śniatała, Alicja (Quality in Sport, 2024)
Introduction Ehlers-Danlos Syndrome (EDS) is a group of connective tissue disorders, the essence of which are abnormalities in the function of collagen. One type of EDS with an unknown genetic basis is the hypermobile form of EDS (hEDS). hEDS manifests mainly in musculoskeletal defects, as well as chronic pain. There is extremely high need to correctly diagnose and then correctly treat patients with hEDS. Initially conservative treatment is used, but if patients fail to achieve relief, surgical treatment is considered. Aim of the study The purpose of the authors was to gather all the information regarding hEDS in terms of surgical treatment. The authors focused mainly on finding the advantages and disadvantages of the various methods and also on collecting information on the indications for choosing the given surgical methods. Materials and methods The methodology of the literature search involved using the keywords: „hypermobile Ehlers-Danlos syndrome”, „shoulder instability”, „joint hypermobility”, „chronic pain” and „Latarjet”. The search terms were entered into the PubMed database. References include systematic reviews, but also clinical trials, as well as case reports. Conclusion Currently available literature does not offer enough information to undertake standardized management of patients with hEDS. Not only is there a lack of studies on groups of patients with hEDS, but also on large groups of patients without hEDS, making it impossible to choose the best method based on the available clinical trials. Moreover, through the lack of such studies, it becomes impossible to truly assess whether patients with hEDS have a higher rate of surgical failure and thus a higher risk of inappropriate management of a specific patient with hEDS.